Cytokine release syndrome in COVID-19: a major mechanism of morbidity and mortality. (21st February 2022) - Que, Yifan; Hu, Chao; Wan, Kun; Hu, Peng; Wang, Runsheng; Luo, Jiang; Li, Tianzhi; Ping, Rongyu; Hu, Qinyong; Sun, Yu; Wu, Xudong; Tu, Lei; et al.
Abstract: The coronavirus disease 2019 (COVID-19) triggered by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) erupted in Hubei Province of China in December 2019 and has become a pandemic. Severe COVID-19 patients who suffer from acute respiratory distress syndrome (ARDS) and multi-organ dysfunction have high mortality. Several studies have shown that this is closely related to the cytokine release syndrome (CRS), often loosely referred to as cytokine storm. IL-6 is one of the key factors and its level is positively correlated with the severity of the disease. The molecular mechanisms for CRS in COVID-19 are related to the effects of the S-protein and N-protein of the virus and its ability to trigger NF-κB activation by disabling the inhibitory component IκB. This leads to activation of immune cells and the secretion of proinflammatory cytokines such as IL-6 and TNF-α. Other mechanisms related to IL-6 include its interaction with GM-CSF and interferon responses. The pivotal role of IL-6 makes it a target for therapeutic agents and studies on tocilizumab are already ongoing. Other possible targets of treating CRS in COVID-19 include IL-1β and TNF-α. Recently, reports of a CRS like illness called multisystem inflammatory syndrome in children (MIS-C) in children have surfaced, with a variable presentation which in some cases resembles Kawasaki disease. It is likely that the immunological derangement and cytokine release occurring in COVID-19 cases is variable, or on a spectrum, that can potentially be governed by genetic factors. Currently, there are no approved biological modulators for the treatment of COVID-19, but the urgency of the pandemic has led to numerous clinical trials worldwide. Ultimately, there is great promise that an anti-inflammatory modulator targeting a cytokine storm effect may prove to be very beneficial in reducing morbidity and mortality in COVID-19 patients.